Beta RBD boost broadens antibody-mediated protection against SARS-CoV-2 variants in animal models - Daniel J. Sheward (Elsevier, 2021)
Summary: Severe acute respiratory syndrome-coronavirus 2 (SARS-CoV-2) variants of concern (VOCs) with resistance to neutralizing antibodies are threatening to undermine vaccine efficacy. Vaccination and infection have led to widespread humoral immunity against the pandemic founder (Wu-Hu-1). Against this background, it is critical to assess the outcomes of subsequent immunization with variant antigens. It is not yet clear whether heterotypic boosts would be compromised by original antigenic sin, where pre-existing responses to a prior variant dampen responses to a new one, or whether the memory B cell repertoire would bridge the gap between Wu-Hu-1 and VOCs. We show, in macaques immunized with Wu-Hu-1 spike, that a single dose of adjuvanted beta variant receptor binding domain (RBD) protein broadens neutralizing antibody responses to heterologous VOCs. Passive transfer of plasma sampled after Wu-Hu-1 spike immunization only partially protects K18-hACE2 mice from lethal challenge with a beta variant isolate, whereas plasma sampled following heterotypic RBD boost protects completely against disease.